Consumer Decision Making Styles in Shopping Malls - An Empirical Study in the Indian Context - Sahoo, Swaroop Chandra; Dash, Prakash Chandra (Indian Journal of Marketing, 2010)
The consumer decision-making process is a complex phenomenon. The purchase of goods or services includes a number of factors that could affect each decision. Consumers are besieged by advertising, news articles, and direct mailings that provide abundant information, much of these are with mixed messages. In addition, increases in the number and variety of goods, stores, and shopping malls and the availability of multicomponent products and electronic purchasing capabilities have broadened the sphere for consumer choice and have complicated the process of decision making. Hence, an attempt has been made in this paper to know about the decision making styles of people in shopping malls.